Career Adaptability: Analysis of Non-Cognitive Factors in University Students - Rahman, Diniy Hidayatur; Multisari, Widya; Probowati, Devy; Bariyyah, Khairul; Tri Hidayatullah, Hengky; Lutfi, Anwar; Kuha, Ariya (KONSELOR, 2024)
This study examines the significance of the paths: (1) from social support to career adaptability, (2) from work value to career adaptability, (3) from self-esteem to career adaptability, (4) from social support to career adaptability via self-esteem, and (5) from work value to career adaptability via self-esteem. A total of 265 students from the Faculty of Education Universitas Negeri Malang who participated in the Asistensi Mengajar (AM) Program were selected using a simple random sampling technique. Four instruments were used to collect data: the Career Adapt-Abilities Scale (CAAS), the Work Value Inventory (WVI), the Self-Esteem Scale, and the Social Support Scale. The data were analysed using path analysis. The findings revealed that all paths have significance values below 0.05, indicating that all proposed paths are acceptable.  The analysis also shows that work value has a direct effect on self-esteem, with a coefficient of 0.160, while social support exhibits a more substantial direct effect on self-esteem, with a coefficient of 0.412. Self-esteem directly influences career adaptability with a coefficient of 0.435. Indirectly, work value impacts career adaptability via self-esteem with a coefficient of 0.070, and social support influences career adaptability via self-esteem with a coefficient of 0.179. The total effects of work value and social support on career adaptability via self-esteem were calculated to be 0.230 and 0.591, respectively. These results suggest that social support has a more pronounced total effect on career adaptability compared to work value, primarily due to its stronger direct effect on self-esteem. The study underscores the critical role of self-esteem as a mediator in enhancing career adaptability through social support and work values.